The Conservation of Kali Pasir Jami’ Mosque in Tangerang, Banten - Yulia Nurliani Lukito; Mushab Abdu Asy Syahid (Universitas Lampung, 2017)
Abstract—The aim of this study is to elaborate the conserving Kali Pasir Jami’ Mosque in Tangerang City, Banten Province that includes the participation of local communities. There is an initial conservation program proposed by the local government but it is not yet clear of how should the collaboration between communities who have done practical conservation and local government who slowly plans the conservation program. The lack of historical documentation of the building and unstructured research done by communities imply a potential threat to the conservation effort and loss of historical values of the mosque. This paper is the result of both qualitative and quantitative approaches such as observation and in-depth interviews in analyzing the conservation of the mosque. The finding of the research shows the important role of local communities in the sustainability of the mosque although there is also an urge to involve experts and government to create the right strategy in conserving the mosque.Keywords—conservation, Kali Pasir Jami’ Mosque, preservation